Heavily nitrogen doped, graphene supercapacitor from silk cocoon. (1st April 2015) - Sahu, Vikrant; Grover, Sonia; Tulachan, Brindan; Sharma, Meenakshi; Srivastava, Gaurav; Roy, Manas; Saxena, Manav; Sethy, Niroj; Bhargava, Kalpana; Philip, Deepu; Kim, Hansung; Singh, Gurmeet; et al.
Abstract: Doping of graphene with nitrogen is of much interest, since it improves the overall conductivity and supercapacitive properties. Besides conductivity, nitrogen doping also enhances the pseudo-capacitance due to fast and reversible surface redox processes. In this work, we have developed a cheap and easy process for synthesizing heavily nitrogen doped graphene (15% nitrogen) from non-mulberry silk cocoon membrane (Tassar, Antheraea mylitta ) by pyrolyzing the cocoon at 400 °C in argon atmosphere. Further we have investigated the performance of this heavily 'nitrogen doped graphene' (NDG) in a supercapacitor device. Our results suggest that NDG obtained from cocoon has improved supercapacitor performance. The improved performance is due to the high electronegativity of nitrogen that forms dipoles on the graphene surface. These dipoles consequently enhance the tendency of graphene to attract charged species to its surface. This is a green and clean synthesis approach for developing electronic materials for energy applications.